(untitled) (Contemporary Journal of Social Science Review, 2025)
This paper seeks to explore the need of portraying Islam as non-violent religious culture in contemporary fiction as a result of the image drawn of them in journalist media as terrorists. It establishes the authors as voicing an identity of Muslims that is different from the one assigned to them by journalist media. This study of the texts will consider the media as a catalyst for tarnishing the image of Muslims to the extent that they, themselves, are reluctant to call themselves practicing Muslims in fear of being mistaken as terrorists. It uses Foucauldian discourse analysis and attempts deconstruction using Jacque Derrida’s model. As this paper will show, these texts not only attempt to discard the general title of Muslims as terrorists, but also discuss stereotypes regarding Islam and the practices of clothing, and beard. Then, the paper will juxtapose the manner in which they are generally perceived to the way they are presented in the novels. This paper discusses Leila Aboulela’s Minaret (2006), Mohsin Hamid’s The Reluctant Fundamentalist (2008), and Orhan Pamuk’s Snow (2004). This choice broadens the scope of this paper because it takes writers from three different parts of the world – Aboulela being a Sudanese, Hamid a Pakistani, and Pamuk a Turk. Moreover, the three novels were written in the 21st century, making this study a discussion of contemporary Muslims.